2013
DOI: 10.1111/php.12064
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Ultraviolet Germicidal Irradiance Luminaires

Abstract: In upper‐room ultraviolet germicidal irradiance (UVGI) design, irradiance is an important characteristic, with two opposing dominant dynamics: high‐level irradiation on the microorganism and minimum levels of irradiance on human skin and eyes. The use of high‐level ray‐tracing procedures is followed in establishing radiance and irradiance levels. The main constants in a room influencing these calculations are the spectral and spatial characteristics of the radiation sources in the inter‐reflecting surfaces ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…This is because the biofilm by microbial filaments will block the effective penetration of UV to deeper layers, preventing UV light from acting deep in microbial colonies. Previous studies have shown that the disinfectant effects of UV light were affected by installation positions, effective distance, and exposure time [80][81][82][83][84][85]. It has been reported that viruses show the lowest resistance to UV light, followed by bacteria, and disinfection of fungi exposed to UV light requires much more time compared to bacteria [86][87][88].…”
Section: Effectiveness Evaluation Of Uv Lightmentioning
confidence: 99%
“…This is because the biofilm by microbial filaments will block the effective penetration of UV to deeper layers, preventing UV light from acting deep in microbial colonies. Previous studies have shown that the disinfectant effects of UV light were affected by installation positions, effective distance, and exposure time [80][81][82][83][84][85]. It has been reported that viruses show the lowest resistance to UV light, followed by bacteria, and disinfection of fungi exposed to UV light requires much more time compared to bacteria [86][87][88].…”
Section: Effectiveness Evaluation Of Uv Lightmentioning
confidence: 99%
“…Upper-air UVC fixtures can vary widely in their luminaire efficiency factors, which rates the performance of emitted UVC from a fixture. Zhang et al (2012) developed a protocol and performed gonioradiometric measurements (i.e., measuring both radiance and irradiance at concurrent angles) for upper-air UVGI fixtures, which is now being used to test total UVC fixture output (Leuschner and Salie 2013). These gonioradiometric measurements are reported in standard IES format compatible with computer-aided design (CAD) lighting software adapted for use with upper room UVC devices (Rudnick et al 2012;Vincent et al 2013).…”
Section: Safety Design Guidancementioning
confidence: 99%